Comparison of Frictional Coefficient and Surface Roughness between Three Different Active Self-ligating Brackets: An Experimental In Vitro Study - Meralda R. Syahdinda, - (Wolters Kluwer Medknow Publications, 2020)
Aim: In orthodontic treatment, the high levels of friction may reduce the effectiveness of the mechanical and decrease tooth movement efficiency. The use of active self-ligating brackets is claimed to possibly reduce friction in orthodontic treatment. The aim of this study was to investigate the three-different active self-ligating orthodontic brackets in frictional coefficient and surface roughness. Materials and Methods: This study was true-experiment laboratory with posttest group design to collect the frictional coefficients data from three different active self-ligating brackets. Friction tests were performed on three different active self-ligating brackets—In-Ovation R, Empower, and BioQuick. Each group consists of seven samples of active self-ligating brackets—and stainless steel wire which has been stored in artificial saliva solutions for 14 days. After the friction coefficients of every sample obtained, the bracket clips were separated from the bodies and set on resin acrylic medias. Surface roughness of the bracket clips was evaluated using the atomic force microscope (AFM). A one-way analysis of variance (ANOVA) followed by Scheffe test for comparisons was performed statistically (P < 0.05). Results: BioQuick and Empower orthodontic brackets produced lower frictional coefficients compared to In-Oviation-R brackets. BioQuick showed least frictional coefficients. Based on the statistical analysis, there was no significant difference of frictional coefficients between Empower and BioQuick. Surface roughness test showed that the clip surface of In-Ovation R produced the maximum roughness, followed by Empower and BioQuick. Conclusion: In-Ovation R brackets offered more frictional coefficients and surface roughness than Empower and BioQuick brackets, whereas BioQuick brackets offered the least among all the brackets studied.